Radical Evil (radikal Böse) - Muchnik, Pablo (Faculdade de Filosofia e Ciências, 2019)
By “evil,” Kant does not designate any set of particularly pernicious acts, but the type of volition that underlies and makes possible immorality in all its forms. The evil person, Kant believes, “makes the incentives of self-love and their inclinations the condition of compliance with the moral law –whereas it is the latter that, as the supreme condition of the satisfaction of the former, should have been incorporated into the universal maxim of the power of choice as the sole incentive” (R 6:36). This inversion of the ethical order of priority does not entail the repudiation of “the moral law (…) in rebellious attitude (by revoking obedience to it)” (R 6:36), but its conditional respect. This fraudulent relation to morality is based on complex strategies of deception, self-deception, and rationalization. The “radical “nature of these tendencies has nothing to do with the intensity or magnitude of observable wrongdoing. Evil’s radicalism is a spatial metaphor intended to designate the locus of immorality (its “root”) in an agent’s “disposition (Gesinnung). What is most baffling the Kantian view is that evil so construed is perfectly compatible with good conduct. Indeed, under the conditions of civilization, Kant believes, it is impossible to distinguish a man of good conduct from a morally good man (RGV 6:30), for the dictates of self-love generally overlap with the prescriptions of duty. The persistence of war, poverty, oppression, and the infinity of vices which cast a dark shadow over the contemporary world speak of the prescience of the Kantian approach.